GIS methodologies for developing conservation strategies : tropical forest recovery and wildlife management in Costa Rica - Savitsky, Basil G.; Lacher, Thomas E. (Biology and resource management in the tropics series., 1998)
-- Michael A. Mares, Oklahoma Museum of Natural History.